OHP-010 Preoperative serum carcinoembryonic antigen levels are associated with histologic subtype, egfr mutations and alk fusion gene in completely resected lung adenocarcinoma patients. (25th February 2017) - Wang, Z; Yang, G; Zhou, C; Yang, S; Lu, H
Abstract : Background: Serum carcinoembryonic antigen (CEA) is usually elevated in lung adenocarcinoma patients, but not in all patients. Lung adenocarcinoma subtypes have been defined by the new International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society international histological classification. Both epidermal growth factor receptor (EGFR) mutation and anaplastic lymphoma kinase (ALK) fusion are the main genes in lung adenocarcinoma. However, the relationship between CEA levels and histologic subtype, EGFR mutations and ALK fusion is still unclear. Purpose: To investigate the relationship between CEA levels and histologic subtype, EGFR mutations as well as ALK fusion, to provide treatment clues for patients with unidentified and undetected EGFR mutations or ALK fusion for clinicians. Material and methods: Preoperative serum CEA levels, postoperative histologic subtype, status of EGFR mutations and ALK fusion protein in 442 completely resected lung adenocarcinoma patients were retrospectively collected and analysed by clinical pharmacists of thoracic medical oncology from January 2014 to December 2015. Results: EGFR mutations were found in 69.9% (309/442) of lung adenocarcinoma patients, and ALK fusion protein in 4.5% (20/442). The EGFR mutation occurred more frequently in non-smokers and lepidic subtype (p=0.001; p=0.001). Higher preoperative serum CEA levels (CEA≥20 ng/mL) were independently associated with EGFR mutations (p<0.001), and lower preoperative serum CEA levels (CEA <20 ng/mL) were independently associated with ALK fusion (p<0.001). Moreover, in patients with CEA level of 20–49 ng/mL, the EGFR mutation rate was 88.2%, which was the highest, compared with CEA level <5 ng/mL, 5–19 ng/mL and ≥50 ng/mL. In addition, all specimens were invasive adenocarcinoma, and were lepidic (18.6%), papillary (15.4%), acinar (52.7%), solid (9.7%), micropapillary (3.2%) or other (0.4%), and levels of CEA in patients with the solid subtype were higher than in other histologic subtypes (p=0.001). Conclusion: Serum CEA levels before operation can be a reference marker to identify histologic subtype, EGFR mutation or ALK fusion in lung adenocarcinoma patients. For the lepidic subtype of lung adenocarcinoma with high serum CEA levels (≥20 ng/mL), EGFR-TKI treatment could be considered, to achieve better clinical efficacy. No conflict of interest